The Influence of Leadership, Motivation, Job Satisfaction, Work Facilities on Employee Performance - Anni Saur Rosida Maris; Moh. Agung Surianto; Nur Cahyadi (Indonesian Vocational Research Journal, 2022)
The purpose of this study was to determine leadership, motivation, job satisfaction, work facilities on employee performance (studies at PT. Varia Usaha Fabrication) Gresik. The sample used the non-probability sampling technique as many as 54 respondents. The analysis technique uses multiple linear regression. The results of multiple linear regression analysis prove that leadership, motivation, job satisfaction, work facilities have a positive effect on employee performance at PT. Varia Usaha Fabrication. These results can be proven that with leadership, motivation, job satisfaction, work facilities that have been implemented can improve employee performance at PT. Varia Usaha Fabrication Gresik.